In Flight Cardiac Arrest (IFCA) Survival: A Concept Analysis (International Journal of Nursing Education, 2022)
Background: The number of inflight medical emergencies has risen in recent years, mainly due to moreand more of us jetting off each year. Sudden Cardiac Arrest can strike at any time. Managing cardiacarrest in flight is really challenging and the survival depends on many factors. It’s been estimated that1000 people die during commercial flights each year. This study clarifies the concept of Inflight CardiacArrest survival by using concept analysis. Methods: To analyze the concept, relevant literature wasanalyzed using Walker and Avant’s concept analysis. Results: The major antecedents of inflight cardiacarrest are cardiac causes, non -cardiac causes, flight conditions and lethal cocktail. Defining attributes ofinflight cardiac arrest survival are in flight attributes, Chain of survival, availability of trained personneland emergency equipment and remaining flight time to destination. Consequences of inflight cardiacarrest are physiologic consequences of victim and emotional consequences of the victim, family,personnel involved and co passengers. Conclusion: Inflight cardiac arrests are increasing in incidence.Lack of a carotid pulse is the gold standard for diagnosing cardiac arrest. Good quality CardiopulmonaryResuscitation and early defibrillation are key factors for inflight cardiac arrest survival.